(3GdJWajds - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe (B: (3TZdfG Gddg hEjGc HWGYJg JhdGc HMaXg hMjGWJg , cfJ PcQJ di C fg GfJgi Edjc McGjI NHQ Wajdi LQJ dg eMGQhI eY fUQ Hf Ydi GdLgVei hCfc CMHHJ Gdhbha Ydjg HdaX aCYdec hbhY GdNHQ Edi HGSfGOg s
(3BNQgG (B:s
(3acf HChGeQg eDJeQG hHRhGLQg eROLQG hdQSheg eJHYG , hHMaXgG eVWdYG Ef TGA Gddg hGdSdGe Ydjc hQMeI Gddg hHQcGJg BNQ GdcJGH hGdMeO ddg hMOg s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B194 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH JjehQ (B559) s
Keywords: (3GdCOHs